Transformasi Layanan Referensi Perpustakaan Universitas Teknokrat Indonesia - Rahmat Iqbal; Yuli Peramita (Al-Ma mun Jurnal Kajian Kepustakawanan dan Informasi, 2023)
Reference service is one of the service facilities provided by the Indonesian Technocrat University library in improving the performance of the library as a center for actual and relevant reference information sources in supporting science and disciplines at the Indonesian Technocrat University. The purpose of this study is to convey an action taken by the technocrat library in carrying out a transformation in one of the reference service areas so as to achieve a maximum performance in providing information guidance to the academic community. Qualitative descriptive methodology is the method that researchers use in this study. Here the researcher analyzes and writes descriptively according to the results of observations, interviews and location analysis that the researchers did at the Indonesian Technocrat University. The result of this research is that the technocrat library has made improvements in creating a total library service performance, especially in reference services. The improvements made are focused on the transformation of information technology and activities in increasing interest in visiting and reading interest in Indonesian technocrat libraries, in accordance with the provisions stipulated by Law No. 43 of 2007 and Government Regulation No. 24 of 2014 concerning Libraries.